2007
DOI: 10.1111/j.1471-6712.2007.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in nursing homes: perception of physically frail elderly residents

Abstract: The purpose of this research was to disclose the characteristics of quality of life as perceived by physically frail but lucid elderly people living in nursing homes to increase the understanding of the phenomenon of quality of life in this setting. Eight elderly residents living in two nursing homes in Iceland were interviewed on two occasions. The interviews were audio-taped and transcribed to generate text for hermeneutic phenomenological analysis. Observation was also undertaken at both nursing homes to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 29 publications
3
64
1
5
Order By: Relevance
“…Studies on the perceived QoL of frail elderly residents with impairments are few [19,20] . Tester's research team found that frail residents in care homes with severe physical and/or mental conditions or disabilities at the end of their lives considered four key inter-related areas for their QoL: sense of self (feeling of being at home, personal appearance and possessions, and preferences for personal space), the care environment (promoting resident autonomy, choices, right to control their lives, and assertiveness), relationships (personal relationships, communication and interaction with residents, relationship with family) and activities (engaging in meaningful activities) [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the perceived QoL of frail elderly residents with impairments are few [19,20] . Tester's research team found that frail residents in care homes with severe physical and/or mental conditions or disabilities at the end of their lives considered four key inter-related areas for their QoL: sense of self (feeling of being at home, personal appearance and possessions, and preferences for personal space), the care environment (promoting resident autonomy, choices, right to control their lives, and assertiveness), relationships (personal relationships, communication and interaction with residents, relationship with family) and activities (engaging in meaningful activities) [19] .…”
Section: Introductionmentioning
confidence: 99%
“…-the ability to participate in the practices of mutual aid and self-care (Aller, & Coeling, 1995;Ball, & Whittington, 2000;Hikoyeda, & Wallace, 2001;Hjaltadottir, & Gustafsdottir, 2007;Orlova, 2015), then for working pensioners, as shown by our research, such parameters include:…”
Section: Resultsmentioning
confidence: 99%
“…En el estudio de Pilkington (17) se hace referencia a la "minuciosidad de la atención". Se confía en que estos profesionales de enfermería atentos y competentes "estén a su lado cuando ellos (las personas mayores), estén enfermos o muriendo" (14).…”
Section: Cualidades Personales Demandadas Al Personal Cuidadorunclassified
“…Los residentes necesitan atribuir a sus personas cuidadoras características similares a las que tendría un amigo: se trata de alguien que contribuye a contrarrestar sus carencias en la vida de la institución, alguien que presta ayuda, que les ofrece atención y en quien se pueda confiar (26). La relación entre los residentes y los cuidadores, establecida a través de un trato más cercano, contribuye a que el mayor se sienta reconocido como una persona (14).…”
Section: La Relación Personal Con Los Cuidadores Y Las Cuidadorasunclassified
See 1 more Smart Citation